Evidence of myogenic vasoconstriction in human bone vasculature - Adina E. Draghici; Matthew R. Ely; Jason W. Hamner (Physiological Reports)
Abstract Despite the critical importance of blood flow for bone, mechanisms regulating bone vasculature are poorly understood. Myogenic vasoconstriction is an important regulatory mechanism that is engaged in most daily activities, but our understanding primarily derives from animal work and/or other vascular beds. In young healthy adults, we employed two levels of leg dependency to engage myogenic vasoconstriction. We measured tibial blood content via near‐infrared spectroscopy (total hemoglobin, ΔtHb) and contrasted it to whole leg flow via popliteal blood flow velocity (LBV) via Doppler ultrasound. Myogenic vasoconstriction was engaged by lowering the leg below heart level (supine to upright to dependent), resulting in increased leg perfusion pressure as assessed by brachial mean pressure adjusted for the hydrostatic pressure from the heart to the tibia. Increased leg perfusion pressure in both positions (Δ30.1 ± 1.36 and Δ42.1 ± 1.16 mmHg; p < 0.01) was accompanied by graded declines in LBV (Δ‐1.88 ± 0.21 and Δ‐2.98 ± 0.27 cm/(s*beat); p < 0.01), indicating whole limb myogenic vasoconstriction. Tibial hemoglobin content did not change (ΔtHb: −0.28 ± 1.76 and 1.26 ± 2.33 μM; p > 0.5), indicating myogenic vasoconstriction was evident, but of lower magnitude compared to the whole leg. These results indicate that myogenic vasoconstriction plays an active role in regulating the tibial vasculature, but with a less robust response compared to the whole leg.